Gimkit-Based Learning Model on the Learning Outcomes of Akidah Akhlak of Class VIII Students of MTs Nurul Islam Sekarbela Mataram - Aisyah; Muhammad Bayu Lutfi (IQRO: Journal of Islamic Education, 2025)
Student learning outcomes, particularly in the subject of Akidah Akhlak, need to be improved by applying more varied and non-monotonous learning models. One such model that can be implemented is the game-based learning model. The aim of this study is to determine the effect of the game-based learning model on the learning outcomes in Akidah Akhlak among eighth-grade students of MTs Nurul Islam Sekarbela Mataram in the 2024/2025 academic year. This research uses a quantitative approach with a quasi-experimental type. The research design employed is a pretest-posttest control-group design. The study was conducted by comparing two classes: a control class and an experimental class. The sample was selected using the cluster random sampling technique, with a total of 62 students in both the control and experimental groups. Data were collected using a multiple-choice test consisting of 25 questions. Final data analysis was performed using independent sample t-test at a significance level of 5% (0.05). Based on the results of the hypothesis test, the obtained significance value (2-tailed) was 0.009, which is smaller than 0.05 (0.009 < 0.05). This means that H ₁ is accepted and H ₀ is rejected, indicating that there is a significant effect of the game-based learning model on the Akidah Akhlak learning outcomes of eighth-grade students at MTs Nurul Islam Sekarbela Mataram in the 2024/2025 academic year.